Financial and Management Challenges Affecting Educational Performance in Basic Schools - Tatsi, samuel; Afful , Kingsley; Adokoh, Emmanuel; Yeng, Enock (International Journal of Educational and Life Sciences, 2024)
The study investigated the management challenges encountered by Basic School Heads in the Lambussie District. Drawing on the transformational leadership theory, the study utilized a pragmatist research philosophy, and the mixed methods approach. A concurrent triangulation mixed methods design was implemented, involving both closed-ended questionnaires and semi-structured interviews with 77 headteachers selected through census sampling. To ensure the reliability of the findings, the Cronbach Alpha coefficient was calculated for the research instrument, yielding a satisfactory value of 0.83. Additionally, trustworthiness was upheld through various measures, including credibility, dependability, confirmability, and transferability. Data analysis was conducted using a combination of statistical measures such as frequency, percentages, mean, mean of means, and standard deviation, as well as thematic analysis for qualitative data. The findings of the study unveiled a myriad of challenges faced by Basic School Heads, particularly in addressing financial constraints, and mitigating the impact of these challenges on educational performance. Recommendations for the Lanbuisse District Educational Directorate include encouraging advocacy efforts are needed to secure increased funding and resource allocation for basic schools, along with transparent financial management systems and exploring alternative funding sources. Furthermore, investments in teacher support, curriculum alignment, and creating a supportive learning environment are essential to mitigate the impact of management challenges on educational performance.